The study of stresses on soil from roadways using plaxis to generate potential energy with piezoelectric - Lim, Alvin John Meng Siang; Sim, Sy Yi; Anting, N.; Prasetijo, Joewono; Noor Hasanah, T. I. T; Goh, H. H.; Buswig, Y. M. Y.; Kang, C. C. (Institute of Advanced Engineering and Science (IAES), 2018)
Environmental resources exploitation is one of the critical problems in environmental engineering. The overuse of environmental resources can lead to a huge impact for the environment and human itself. The problems of extracting and processing of raw materials from earth such as mining, steam power and machinery has increased year by year and this is the main reason that the resources has become very limited for the future generations to use them. This study is focused in designing a roadway through software analysis which will use the concept of piezoelectricity that will convert the stress energy from the roadways into electrical energy. A software which is called PLAXIS 2D will be used to simulate the stresses from the roadway which are caused by moving vehicle loading. The parameters of laterite and clay soil such as Specific Gravity, Liquid Limit, Friction Angle and Cohesion are obtained from the past research is needed for the input of the software. The loading application in the PLAXIS 2D uses the Mohr-Coulomb failure criterion in which fully drained and axisymmetric conditions were assumed. A non-uniform grid with 1726 elements was performed for the calculations on a 2-dimensional cross-sections of 11m x 3m roadway. The stresses resulted from the software are used to determine the value of stresses required for the piezoelectric to convert the stress energy into electrical energy.